Pelatihan Pembuatan Games dengan Scratch Untuk Siswa SMA Wachid Hasyim 5 Surabaya - Sari, Mamik Usniyah; Muhandhis, Isnaini; Wijaya, Nicholas; Murdani, Muhammad Harist; Atmojo, Suryo; Dewi, Suzana; Ritonga, Alven Safik; Widhiyanta, Nurwahyudi (Fakultas Teknik-Universitas Wijaya Putra, 2024)
In the increasingly developing digital era, there are several computer skills that high school students must have. One of them is understanding the basics of programming and software development. This service program aims to introduce basic programming concepts and systematic logical thinking to Wachid Hasyim 5 High School students and motivate students to learn computers as a basic skill that must be possessed in the current era by creating game programs with Scratch. The implementation of this training was carried out using a participatory approach where the implementing team provided direct learning and assistance to participants. Mentoring is provided until students can master the material for making games with Scratch. The results of this service program are an increase in students' understanding of the basics of computer programming and an increase in students' skills in creating games with Scratch. This is proven by the post-test results which increased after the training was implemented.